Magnetically-enhanced temporary plugging agent as well as preparation method and application thereof
By introducing magnetic particles into the temporary plugging agent and strengthening their magnetic properties, and adhering an elastic material coating outside the particles, the problem of weak interaction force of the temporary plugging agent of the degradable material-based particles is solved, and a more efficient temporary plugging effect and stronger sealing strength are achieved.
Patent Information
- Application Number
- CN202311283335.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-10-07
AI Technical Summary
The interaction force of ordinary degradable material-type particles is weak, resulting in some particles being unable to effectively accumulate and build bridges in formation cracks, which is relatively low.
By combining magnetic particles into the temporary blocking agent base, the attractiveness of the temporary blocking agent is increased, and the permanent magnetism of the particles is strengthened through a magnetic charger to achieve the temporary blocking agent that is magnetic attraction. At the same time, the magnetic particle content is controlled to regulate the attraction between particles, and an elastic material coating is attached to the particles to improve the sealing effect.
The efficiency of temporary plugging agent aggregation and bridge formation in cracks is improved, the efficiency of temporary plugging is enhanced, and effective sealing is maintained in high-temperature water environment without affecting subsequent production.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of temporary plugging agents for fracturing, and in particular relates to a magnetically enhanced temporary plugging agent and a preparation method and application thereof. Background Art
[0002] The increasing shortage of energy has made crude oil play an important role in modern industry, and a stable supply of crude oil is crucial to economic and social development. Formation fracturing is a key means to improve oil and gas recovery.
[0003] Fracturing is a process of injecting high-pressure liquid into the ground to crack the formation, thereby enhancing the production channels of oil or natural gas, or the injection channels of oil displacement agents, thereby improving the oil and gas recovery capacity.
[0004] During fracturing, in the same section, the formation opening pressures at different locations are different. Opening the cracks first will consume a lot of liquid, which will reduce the cracking effect at the later opening positions, thus affecting the cracking effect of fracturing. Temporary plugging material is a polymer material for fracturing developed to improve the cracking effect.
[0005] During fracturing, the addition of temporary plugging materials can seal the cracks that are opened first, divert the flow to the unopened position, and improve the fracturing effect. After the construction is completed, under the influence of formation temperature and water, the temporary plugging materials can slowly degrade and become ineffective. After degradation, they will not block the formation and cracks, and will not affect subsequent production.
[0006] Degradable polymers such as polyglycolide and polylactide are used as temporary plugging materials due to their good mechanical properties and degradation characteristics. Temporary plugging agents used to plug cracks are mainly mixed with degradable materials of different particle sizes. After being brought into the cracks by the liquid flow, they form bridges and are retained to plug the cracks.
[0007] However, due to the small interaction between the resin particles of the degradable polymer, a large number of resin particles will flow into the deep cracks with the flow of the fracturing fluid before bridging and plugging occurs, and the actual efficiency of bridging and plugging the cracks is low. A large number of particles are ineffectively dispersed in the cracks and cannot gather to form bridges to produce effective plugging. Summary of the invention
[0008] The present invention mainly solves the problem that the interaction force of ordinary degradable material particle temporary plugging agents is weak, and some particles cannot effectively aggregate and bridge after the liquid flows into the formation, thus resulting in low efficiency. In order to solve the above problems, the present invention provides a magnetically enhanced temporary plugging agent and its preparation method and application, wherein the attraction between the temporary plugging agents is increased by compounding magnetic particles into the temporary plugging agent matrix. The magnetic particles are introduced into the temporary plugging agent matrix, and the permanent magnetism of the particles is strengthened by a magnetizer, thereby realizing a temporary plugging agent with magnetic attraction. At the same time, the control of the content of magnetic particles can regulate the attraction between the particles. The temporary plugging agent can be dispersed in the solution under the high shear action of the fracturing construction, but when entering the formation cracks, the flow rate is reduced, and the temporary plugging agents are aggregated due to the magnetic interaction, which effectively enhances the aggregation and bridging of the temporary plugging agents in the cracks, and improves the temporary plugging efficiency. In addition, in order to effectively block the gaps between the temporary plugging particle accumulation bodies and improve the blocking effect, the present invention also attaches an elastic material coating to the outside of the temporary plugging particles, and the coating has a low glass transition temperature to give it elasticity. When the particles are accumulated, the particle accumulation gaps can be effectively blocked to achieve efficient blocking. At the same time, in the high-temperature water environment of the oil reservoir, the coating can be slowly dissolved without affecting the degradation of the temporary plugging material.
[0009] In one aspect, the present invention provides a magnetically enhanced temporary plugging agent, which comprises a temporary plugging agent matrix and modified magnetic particles dispersed in the temporary plugging agent matrix.
[0010] In the present invention, the temporary plugging agent matrix is selected from a degradable polymer, preferably one of polyglycolide, polylactide, polybutylene succinate, polycaprolactone, polybutylene terephthalate-adipate, polybutylene terephthalate, polybutylene succinate adipate, polymethyl ethylene carbonate, polyhydroxyalkanoate or a mixture thereof or a copolymer of their structural units.
[0011] In the present invention, the modified magnetic particles are magnetic particles modified by a compatibilizer. Preferably, the compatibilizer is selected from at least one of epoxy compounds, silane compatibilizers, copolymers containing maleic acid or its anhydride or its amide, titanate compatibilizers, aluminate compatibilizers, zirconate esters, borates, and aluminum-titanium composite compatibilizers; more preferably, based on 100 parts by weight of the magnetic particles, the compatibilizer is 0.1%-1% by weight, preferably 0.2%-0.6% by weight.
[0012] In the present invention, the magnetic particles are selected from at least one of ferrite, neodymium iron boron, samarium cobalt, aluminum nickel cobalt, manganese aluminum carbon, and iron chromium cobalt; and / or the particle size of the magnetic particles is 100 to 800 nm, preferably 100 to 500 nm; and / or, in the magnetic enhanced temporary plugging agent, based on 100 parts by weight of the temporary plugging matrix, the modified magnetic particles are 5 to 30 parts by weight.
[0013] In the present invention, the magnetically enhanced temporary plugging agent further comprises an elastic material coating coated on the surface of the temporary plugging agent matrix; preferably, the elastic material is selected from polymers containing ester bonds in the side chains, preferably polyvinyl acetate; more preferably, based on 100wt% of the temporary plugging agent matrix and the modified magnetic particles, the elastic material coating is 1 to 10wt%, preferably 3 to 5wt%.
[0014] In the present invention, the magnetically enhanced temporary plugging agent further optionally includes an auxiliary agent; preferably, the auxiliary agent is selected from at least one of an antioxidant, a stabilizer, and an anti-hydrolysis agent; more preferably, based on 100 parts by weight of the temporary plugging agent matrix, the antioxidant is 0.1%-1% by weight, the stabilizer is 0.001%-0.1% by weight, and the anti-hydrolysis agent is 0.1%-1% by weight.
[0015] The second aspect of the present invention provides a method for preparing a magnetically enhanced temporary plugging agent, comprising: melt-blending and extruding the temporary plugging agent matrix, the modified magnetic particles and the optional auxiliary agent to form granules, and then magnetizing and optionally pulverizing to obtain the magnetically enhanced temporary plugging agent.
[0016] In the present invention, the modified magnetic particles are obtained by mixing the compatibilizer with the magnetic particles, raising the temperature to 40-100° C., heat-treating, and drying to obtain the modified magnetic particles.
[0017] In the present invention, the magnetization treatment is carried out as follows: magnetization is performed for more than 3 seconds in a magnetizer with a magnetization voltage of 0-2000 V, preferably excluding 0 V.
[0018] In the present invention, after the magnetization and optional pulverization, the temporary plugging agent is immersed in a solution containing the elastic material, filtered out, and dried to obtain the magnetically enhanced temporary plugging agent.
[0019] The third aspect of the present invention provides the use of the magnetically enhanced temporary plugging agent in fracturing.
[0020] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The magnetically enhanced temporary plugging agent obtained by the technical solution of the present invention has permanent magnetism. Therefore, when the fracturing fluid enters the formation fracture, when the flow rate decreases, the particles aggregate with each other, strengthening the plugging and bridging of the particles in the fracture, thereby improving the temporary plugging efficiency;
[0023] (2) The magnetic properties of the magnetically enhanced temporary plugging agent obtained by the technical solution of the present invention provide the interaction force between particles, which can be broken up and separated under high shear, without affecting the solution preparation and pipeline transportation during fracturing construction;
[0024] (3) The magnetically enhanced temporary plugging agent obtained by the technical solution of the present invention will degrade and become ineffective after long-term service under the action of water and heat in the formation. Finally, the polymer matrix will degrade into small molecules, while the magnetic particles will be rigid particles with small particle size, which can be discharged with the backflow or formation production fluid without affecting subsequent construction and production;
[0025] (4) Compared with ordinary unmodified degradable particles, the magnetic enhanced temporary plugging agent obtained by the technical solution of the present invention has a higher retention rate in the artificial fracture plugging experiment, which significantly improves the utilization efficiency of the temporary plugging material and slightly increases the plugging strength;
[0026] (5) In order to effectively block the gaps between temporary plugging particle accumulation bodies and improve the plugging effect, the present invention also attaches an elastic material coating to the temporary plugging particles. The coating has a low glass transition temperature and gives it elasticity. When the particles are accumulated, it can effectively block the gaps between the particles and achieve efficient plugging. At the same time, in the high-temperature water environment of the oil reservoir, the coating can be slowly dissolved without affecting the degradation of the temporary plugging material;
[0027] (6) The present invention modifies a layer of elastic material on the surface of the temporary plugging particles, so that the magnetically enhanced temporary plugging agent can maintain a high retention rate and temporary plugging strength even in a relatively low dispersion system (for example, a dispersion system of less than 10%, or a dispersion system of less than 9%, or a dispersion of less than 8%). DETAILED DESCRIPTION
[0028] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.
[0029] One of the purposes of the present invention is to provide a magnetically enhanced temporary plugging agent, which comprises an elastic coating of a temporary plugging agent matrix and modified magnetic particles dispersed in the temporary plugging agent matrix.
[0030] In a preferred embodiment, the temporary plugging agent matrix is selected from degradable polymers.
[0031] In a further preferred embodiment, the degradable polymer is selected from one of polyglycolide, polylactide, polybutylene succinate, polycaprolactone, polybutylene terephthalate-adipate, polybutylene terephthalate, polybutylene succinate adipate, polymethyl ethylene carbonate, polyhydroxyalkanoate, or a mixture of multiple thereof or a copolymer of their structural units.
[0032] In a further preferred embodiment, the melt index of the degradable polymer is above 1 g / 10 min.
[0033] In a preferred embodiment, the modified magnetic particles are magnetic particles modified by a compatibilizer.
[0034] In a further preferred embodiment, the compatibilizer is selected from at least one of epoxy compounds, silane compatibilizers, copolymers containing maleic acid or its anhydride or amide, titanate compatibilizers, aluminate compatibilizers, zirconate esters, borates, and aluminum-titanium composite compatibilizers.
[0035] In a further preferred embodiment, the compatibilizer is selected from at least one of 3-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltriethoxysilane.
[0036] In a preferred embodiment, based on 100 parts by weight of the magnetic particles, the compatibilizer is 0.1%-1% by weight, preferably 0.2%-0.6% by weight, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1% by weight.
[0037] Among them, adding a compatibilizer can increase the bonding strength between the magnetic particles and the matrix material, improve the dispersion effect of the magnetic particles, increase the strength of the composite material, and reduce the influence of the interface defects between the magnetic particles and the matrix material on the mechanical properties of the material.
[0038] In a preferred embodiment, the magnetic particles are selected from at least one of ferrite, neodymium iron boron, samarium cobalt, aluminum nickel cobalt, manganese aluminum carbon, and iron chromium cobalt.
[0039] In a further preferred embodiment, the particle size of the magnetic particles is 100-800 nm, preferably 100-500 nm (more preferably excluding 100 nm), for example 150 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm or 800 nm.
[0040] Among them, since the magnetic particles are used as temporary plugging agents, the particle size of the magnetic particles cannot be too large. The reasons are: (1) If the particle size is too large, when the matrix material degrades, the magnetic particles will settle seriously in the water, which will be detrimental to their return to the ground with the return fluid; (2) If the particle size is too large, it may cause blockage in the formation near the wellbore, affecting subsequent construction.
[0041] In a preferred embodiment, in the magnetically enhanced temporary plugging agent, based on 100 parts by weight of the temporary plugging matrix, the modified magnetic particles are 5 to 30 parts by weight, for example, 5 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, 18 parts by weight, 20 parts by weight, 22 parts by weight, 25 parts by weight, 28 parts by weight or 30 parts by weight. Among them, since the temporary plugging agent is used in the field of fracturing, it will first enter the well with the fracturing fluid at a high shear flow rate, and then enter the cracks that have been opened (the flow rate in the cracks is very slow). Then, in order to adapt to this special application scenario, the inventors found after a large number of experiments that when the content of the modified magnetic particles is controlled at 5 to 30 parts by weight, it has a better effect.
[0042] Specifically, controlling the modified magnetic particles within the above range solves the problem of how to effectively disperse the temporary plugging agent in the liquid during fracturing construction after giving it permanent magnetism. Specifically, by controlling the content of magnetic particles in the composite material, the interaction force between the temporary plugging agents is adjusted so that the interaction force between the particles can meet the following conditions: 1) During the preparation, stirring, and pipe transportation of high-shear solutions, the particles can be dispersed by the high-shear liquid flow and enter the underground with the liquid flow; 2) When the liquid flow enters the formation fracture, the shear rate decreases, and the magnetic attraction between the particles can effectively give the particles the ability to agglomerate, helping to increase the probability of bridging and plugging of the particles and improving the sealing effect; 3) When the degradable polymer is degraded and ineffective under the action of water and heat, the modified magnetic particles, as a small-diameter rigid particle, can be discharged with the backflow or formation production fluid, and will not affect subsequent construction and production.
[0043] In a preferred embodiment, the magnetically enhanced temporary plugging agent further comprises an elastic material coating coated on the surface of the temporary plugging agent matrix.
[0044] In a further preferred embodiment, the glass transition temperature of the elastic material is lower than the glass transition temperature of the temporary plugging agent matrix.
[0045] In a further preferred embodiment, the elastic material is selected from a material with a glass transition temperature of 40-60°C, preferably 45-55°C, for example 40°C, 45°C, 50°C, 55°C or 60°C.
[0046] The elastic material is water-soluble at the target formation temperature (when it is polyvinyl acetate, its side groups are water-soluble after degradation at the target formation temperature).
[0047] In a preferred embodiment, the elastic material is selected from polymers having ester bonds in the side chains, such as polyvinyl acetate.
[0048] In a further preferred embodiment, the molecular weight of the elastic material is 10,000 to 100,000, preferably 15,000 to 50,000.
[0049] Most preferably, the elastic material is a polymer with a molecular weight of 15,000-50,000 and an ester bond in the side chain (such as polyvinyl acetate), and a degree of alcoholysis of 30%-60%.
[0050] In a preferred embodiment, based on 100 wt % of the temporary plugging agent matrix and the modified magnetic particles, the elastic material coating is 1 to 10 wt %, preferably 3 to 5 wt %.
[0051] In a preferred embodiment, the magnetically enhanced temporary plugging agent further includes an auxiliary agent.
[0052] In a further preferred embodiment, the auxiliary agent is selected from at least one of an antioxidant, a stabilizer, and an anti-hydrolysis agent.
[0053] In a further preferred embodiment, the antioxidant is selected from at least one of phosphate esters and hindered phenol compounds; and / or the stabilizer is selected from at least one of dibutyltin maleate, dibutyltin dilaurate, dibutyltin laurate maleate, di-n-octyltin maleate, di-n-octyltin dilaurate, and di-n-octyltin bis(isooctyl thioglycolate); and / or the anti-hydrolysis agent is selected from bis(2,6-diisopropylphenyl)carbodiimide.
[0054] Among them, stabilizers are mainly used to improve thermal stability at high temperatures, mainly to improve stability during processing. Anti-hydrolysis agents are mainly used to delay degradation. Degradable polymers are ultimately meant to be degraded, but the faster the better. In order to adjust the degradation rate, anti-hydrolysis agents are added.
[0055] In a preferred embodiment, based on 100 parts by weight of the temporary plugging agent matrix, the antioxidant is 0.1%-1% by weight, preferably 0.2%-0.6% by weight; the stabilizer is 0.001%-0.1% by weight, preferably 0.01%-0.05% by weight; the anti-hydrolysis agent is 0.1%-1% by weight, preferably 0.2%-0.6% by weight.
[0056] For example, based on 100 parts by weight of the temporary plugging agent matrix, the antioxidant is 0.1%, 0.2%, 0.4%, 0.6% or 1% by weight; the stabilizer is 0.001%, 0.005%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08% or 0.1% by weight; the anti-hydrolysis agent is 0.1%, 0.2%, 0.4%, 0.6%, 0.8% or 1% by weight.
[0057] In a preferred embodiment, the magnetically enhanced temporary plugging agent can be of any range of values, which is mainly estimated based on the size range of underground fractures, for example, the particle size is 20 to 240 meshes.
[0058] In a preferred embodiment, the magnetically enhanced temporary plugging agent has magnetism, preferably permanent magnetism.
[0059] Wherein, the magnetically enhanced temporary plugging agent is temporary plugging agent particles that have been magnetized.
[0060] In a further preferred embodiment, the magnetization is carried out for more than 3 seconds in a magnetizer having a magnetizing voltage of 0-2000 V and preferably excluding 0 V.
[0061] Among them, permanent magnetism is formed after sufficient magnetization.
[0062] The second object of the present invention is to provide a method for preparing the magnetically enhanced temporary plugging agent described in the first object of the present invention, comprising: melt-blending, extruding and granulating the temporary plugging agent matrix, the modified magnetic particles and the optional auxiliary agent, and then magnetizing and crushing to obtain the magnetically enhanced temporary plugging agent.
[0063] In a preferred embodiment, the modified magnetic particles are obtained by mixing the compatibilizer with the magnetic particles, raising the temperature to 40-100°C (e.g., 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C), heat-treating, and drying to obtain the modified magnetic particles.
[0064] In a further preferred embodiment, the mixing is performed as follows: the compatibilizer is dispersed in an aqueous alcohol solution, and then the magnetic particles are added and stirred.
[0065] Preferably, the alcohol is selected from C1-C6 alkyl alcohols, such as ethanol.
[0066] In a further preferred embodiment, the heat preservation treatment is carried out for 10 to 40 hours, preferably 15 to 35 hours, for example, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours or 40 hours.
[0067] In a preferred embodiment, the extrusion is carried out at 150°C to 250°C, preferably 175°C to 240°C, for example 150°C, 160°C, 180°C, 200°C, 220°C, 240°C or 250°C.
[0068] For example, when the degradable matrix is polyglycolide, the extrusion temperature is 220°C to 240°C, and when the degradable matrix is polylactide, the extrusion temperature is 175°C to 200°C.
[0069] In a preferred embodiment, the extrusion is carried out in an extruder, and the rotation speed of the extruder is 50rpm to 1000rpm, preferably 100rpm to 500rpm, more preferably 150rpm to 200rpm, for example, 50rpm, 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm or 1000rpm.
[0070] In a preferred embodiment, the magnetization treatment is performed as follows: magnetization is performed in a magnetizer with a magnetization voltage of 0-2000V for more than 3 seconds.
[0071] In a preferred embodiment, the particles are crushed into 20-240 mesh particles.
[0072] In a preferred embodiment, after the magnetization and optional crushing, magnetic pre-treated particles are obtained, the magnetic pre-treated particles are immersed in a solution containing the elastic material, then filtered out, and then dried to obtain the magnetically enhanced temporary plugging agent.
[0073] In a further preferred embodiment, the concentration of the solution of the elastic material is 5-50wt%, preferably 10-30wt%, for example 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%.
[0074] In a further preferred embodiment, the solvent in the solution of the elastic material is an organic solvent, such as at least one of methanol, acetone, chloroform, ethyl acetate and benzene.
[0075] The third object of the present invention is to provide the magnetically enhanced temporary plugging agent described in the first object of the present invention or to use the magnetically enhanced temporary plugging agent described in the second object of the present invention in fracturing, specifically for use in oil and gas reservoir fracturing reconstruction.
[0076] The magnetic properties of the magnetically enhanced temporary plugging agent of the present invention provide an interaction force between particles, which can be broken up and separated under high shear, without affecting the solution preparation and pipeline transportation in the fracturing construction; the magnetically enhanced temporary plugging agent of the present invention has permanent magnetism, so after the fracturing fluid enters the formation fracture, when the flow rate decreases, the particles aggregate with each other, strengthening the blocking and bridging of the particles in the fracture and improving the temporary plugging efficiency; the magnetically enhanced temporary plugging agent of the present invention will degrade and become ineffective after long-term service under the action of water and heat in the formation, and finally the polymer matrix will degrade into small molecules, while the magnetic particles are rigid particles with small particle size, which can be discharged with the backflow or formation production fluid, without affecting subsequent construction and production.
[0077] Compared with ordinary unmodified degradable particles, the magnetic enhanced temporary plugging agent of the present invention has a higher retention rate in the artificial fracture plugging experiment, which significantly improves the use efficiency of the temporary plugging agent; and when the injection amount of the temporary plugging agent is reduced, the plugging strength of the magnetic enhanced temporary plugging agent of the present invention will not be reduced.
[0078] Example
[0079] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0080] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0081] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0082] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0083] [Example 1]
[0084] Preparation of modified magnetic particles:
[0085] Dissolve 0.4 parts of compatibilizer KH550 in 20g of 95% ethanol aqueous solution to prepare a uniform solution, add 100 parts of 100nm ferroferric oxide magnetic particles and stir evenly, seal and keep warm at 70°C for 24 hours, and dry at 120°C for 4 hours to prepare 100nm modified magnetic particles (the compatibilizer is only a surface treatment and will not significantly change the particle size).
[0086] Preparation of magnetic enhanced temporary plugging agent:
[0087] 100 parts by weight of polyglycolide, 0.3 parts by weight of pentaerythritol diphosphite di(2,4-di-tert-butylphenyl) ester, 0.01 parts by weight of dibutyltin maleate, 0.4 parts by weight of bis(2,6-diisopropylphenyl)carbodiimide, and 20 parts by weight of the above modified magnetic particles are melt blended and extruded for granulation, wherein the extrusion temperature is 220°C to 240°C, and the extruder speed is 350rpm. After extrusion granulation, the particles are magnetized for 4 seconds in a magnetizer with a magnetizing voltage of 2000V, and then crushed into particles between 20-240 meshes, and the particles are immersed in a methanol solution of polyvinyl acetate with a concentration of 20% for 1 minute, filtered out, and dispersed and spread on a tray. After hot air drying at 50°C for 30 minutes, the dried particles are collected, and the adhered particles are squeezed and rubbed apart, and the particles between 20-240 meshes are sieved as products.
[0088] [Example 2]
[0089] Preparation of modified magnetic particles:
[0090] 0.4 parts of compatibilizer KH550 were dissolved in 20g of 95% ethanol aqueous solution to prepare a uniform solution, and 100 parts of 500nm aluminum-nickel-cobalt alloy magnetic particles were added and stirred evenly, then sealed and kept warm at 70°C for 24 hours and dried at 120°C for 4 hours to prepare 500nm modified magnetic particles.
[0091] Preparation of magnetic enhanced temporary plugging agent:
[0092] 100 parts by weight of polyglycolide, 0.5 parts by weight of tris(2,4-di-tert-butylphenyl)phosphite, 0.03 parts by weight of dibutyltin maleate, 0.3 parts by weight of bis(2,6-diisopropylphenyl)carbodiimide, and 30 parts by weight of the above modified magnetic particles are melt blended and extruded for granulation, wherein the extrusion temperature is 220°C to 240°C and the extruder speed is 400rpm. After extrusion granulation, the particles are magnetized for 3 seconds in a magnetizer with a magnetizing voltage of 2000V, and then crushed into particles between 20-240 meshes, and the particles are immersed in a methanol solution of polyvinyl acetate with a concentration of 20% for 1 minute, filtered out, and spread on a tray. After hot air drying at 50°C for 30 minutes, the dried particles are collected, and the adhered particles are squeezed and rubbed apart, and the particles between 20-240 meshes are sieved as products.
[0093] [Example 3]
[0094] Preparation of modified magnetic particles:
[0095] 0.4 parts of compatibilizer KH550 were dissolved in 20g of 95% ethanol aqueous solution to prepare a uniform solution, and 100 parts of 100nm NdFeB alloy magnetic particles were added and stirred evenly, then sealed and kept warm at 70°C for 24 hours and dried at 120°C for 4 hours to prepare 100nm modified magnetic particles.
[0096] Preparation of magnetic enhanced temporary plugging agent:
[0097] 100 parts by weight of polylactide, 0.4 parts by weight of pentaerythritol diphosphite di(2,4-di-tert-butylphenyl) ester, 0.02 parts by weight of dibutyltin maleate, 0.2 parts by weight of bis(2,6-diisopropylphenyl)carbodiimide, and 20 parts by weight of the above modified magnetic particles are melt blended and extruded for granulation, wherein the extrusion temperature is 175°C to 200°C, and the extruder speed is 350rpm. After extrusion granulation, the particles are magnetized for more than 3.5 seconds in a magnetizer with a magnetizing voltage of 2000V, and then crushed into particles between 20 and 240 meshes, and the particles are immersed in a methanol solution of polyvinyl acetate with a concentration of 20% for 1 minute, filtered out, dispersed and spread on a tray, and dried with hot air at 50°C for 30 minutes, and the dried particles are collected, and the adhered particles are squeezed and rubbed, and the particles between 20 and 240 meshes are sieved as the product.
[0098] [Example 4]
[0099] Preparation of modified magnetic particles:
[0100] 0.4 parts of compatibilizer KH550 were dissolved in 20g of 95% ethanol aqueous solution to prepare a uniform solution, and 100 parts of 500nm iron-chromium-cobalt alloy magnetic particles were added and stirred evenly, then sealed and kept warm at 70°C for 24 hours and dried at 120°C for 4 hours to prepare 500nm modified magnetic particles.
[0101] Preparation of magnetic enhanced temporary plugging agent:
[0102] 100 parts by weight of polylactide, 0.2 parts by weight of tris(2,4-di-tert-butylphenyl)phosphite, 0.05 parts by weight of dibutyltin maleate, 0.5 parts by weight of bis(2,6-diisopropylphenyl)carbodiimide, and 30 parts by weight of the above modified magnetic particles are melt blended and extruded for granulation, wherein the extrusion temperature is 175°C to 200°C and the extruder speed is 400rpm. After extrusion granulation, the particles are magnetized for 3 seconds in a magnetizer with a magnetizing voltage of 2000V, and then crushed into particles between 20-240 meshes, and the particles are immersed in a methanol solution of polyvinyl acetate with a concentration of 20wt% for 1min, filtered out, and spread on a tray. After hot air drying at 50°C for 30min, the dried particles are collected, the adhered particles are squeezed and rubbed, and the particles between 20-240 meshes are sieved as products.
[0103] [Comparative Example 1]
[0104] The process of Example 1 was repeated, except that the modified magnetic particles were not added during melt extrusion, and other conditions remained unchanged.
[0105] [Comparative Example 2]
[0106] The process of Example 4 was repeated, except that: (1) the modified magnetic particles were not added during melt extrusion; (2) the amount of antioxidant was 0.2 parts by weight; (3) the amount of stabilizer was 0.05 parts by weight; and (4) the amount of anti-hydrolysis agent was 0.5 parts by weight.
[0107] [Comparative Example 3]
[0108] The process of Example 4 was repeated, except that when preparing the magnetic strengthening temporary plugging agent, the amount of modified magnetic particles was changed to 40 parts by weight, and other conditions remained unchanged.
[0109] [Comparative Example 4]
[0110] The process of Example 4 was repeated, except that, when preparing the magnetic strengthening temporary plugging agent, the final coating process of the polyvinyl acetate coating was not performed.
[0111]
Experimental Example 1
[0112] The temporary plugging agents prepared in the examples and comparative examples were used to conduct temporary plugging experiments in artificial fracture cores. The specific steps are as follows:
[0113] Take partially hydrolyzed polyacrylamide (hydrolysis degree 20%) with a molecular weight of 15-17 million, configure it into an aqueous solution of 1000ppm, disperse the temporary plugging agent in the aqueous solution, and stir to configure it into a dispersed system with a temporary plugging agent content of 10%. The dispersed system is loaded into a piston container with mechanical stirring, and the dispersed system is injected into the artificially fractured core by a constant speed pump at a stirring speed of 1000rpm. The injection rate is 5ml / min. The artificially fractured core is 10cm long and 2.5cm in diameter. The crack width is controlled to 1mm by a copper sheet. Inject until the highest pressure point, and record the pressure as the plugging strength. When the pressure exceeds the maximum plugging pressure, the temporary plugging particles fail, and the pressure begins to drop, immediately close the valve and stop injection. Collect the produced fluid and filter the temporary plugging agent therein to record it as the amount of temporary plugging agent flowing out. Take out the uninjected dispersed system and filter it to calculate the remaining temporary plugging agent. The difference between the initial amount and the remaining amount is the injected temporary plugging agent. The difference between the injected temporary plugging agent and the outflowing temporary plugging agent and the ratio of the injected temporary plugging agent are calculated as the retention rate of the temporary plugging agent. The results are shown in Table 1.
[0114] The water dispersion system prepared in the embodiment and the comparative example was configured with a content of 10%, and sealed and kept warm at 90°C for 48 hours. The particles lost their mechanical properties and broke into fine powder. The degradation products had no ability to block cracks, etc., and did not affect subsequent construction and production. However, if the magnetic particles used have a particle size higher than 800nm, then after the temporary plugging agent is degraded, the magnetic particles higher than 800nm will settle seriously, which will affect subsequent construction and production.
[0115] Table 1 Retention rate and temporary plugging strength of temporary plugging agents prepared in the examples and comparative examples in a 10% dispersion system
[0116] Retention rate % Plugging strength MPa Example 1 86.2 41.4 Example 2 90.1 42.6 Example 3 85.4 32 Example 4 91.6 32.3 Comparative Example 1 62.1 40.7 Comparative Example 2 59.2 31.5 Comparative Example 3 ----- ---- Comparative Example 4 90.7 31
[0117] As can be seen from Table 1, the attraction between particles of the temporary plugging agent is increased after magnetic enhancement. Therefore, in the temporary plugging experiment, the retention rate of the temporary plugging agent in the crack is significantly improved. The lowest retention rate of the sample in the embodiment is 23% higher than that in the comparative example 1, which proves that the system obtained by the present invention effectively improves the use efficiency of the temporary plugging agent.
[0118] In Comparative Example 3, the magnetic particle content is higher than that in Example 4. At a mechanical stirring speed greater than 1000 rpm, the magnetic particles aggregate into clumps and cannot be effectively dispersed in the solution. Therefore, they cannot be effectively injected, the temporary plugging of the cracks cannot be achieved, and no effective data can be obtained.
[0119] Comparative Example 4 does not introduce a polyvinyl acetate coating into the technical solution of the present invention. Therefore, the gaps where the temporary blocking particles are accumulated cannot be effectively blocked and filled, and the blocking strength is affected to a certain extent.
[0120] The above data confirm the effectiveness and superiority of the technical solution of the present invention, which can enhance the efficiency of using temporary plugging particles in fracturing construction and provide a more efficient solution for formation transformation and oil and gas field production increase.
[0121]
Experimental Example 2
[0122] The temporary plugging experiment of [Experimental Example 1] was repeated, except that the temporary plugging agent content was 8% in a dispersed system. The results are shown in Table 2 below.
[0123] Table 2 Retention rate and temporary plugging strength of temporary plugging agents prepared in the examples and comparative examples in 8% dispersion system
[0124] Retention rate % Plugging strength MPa Example 1 85.8 41.2 Example 2 89.8 41.7 Example 3 85.3 31.8 Example 4 91.2 31.9 Comparative Example 1 11.4 0.0 Comparative Example 2 13.2 0.0 Comparative Example 3 ----- ---- Comparative Example 4 89.7 27.4
[0125] As can be seen from Table 2, when the temporary plugging agent content is reduced to 8%, the sample of the embodiment can still have a high retention rate and plugging strength, while the comparative examples 1 and 2 cannot effectively establish a pressure difference, the plugging strength is 0, and the retention rate is only 11.4% and 13.25, and the cracks cannot be effectively plugged. Comparative example 4 has a higher retention rate due to the presence of magnetic particles, but due to the absence of coating, the plugging has a certain degree of decline, and the decline is more obvious relative to the data with a temporary plugging particle content of 10%.
[0126] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A magnetically enhanced temporary plugging agent, comprising a temporary plugging agent matrix and modified magnetic particles dispersed in the temporary plugging agent matrix.
2. The magnetic strengthening temporary plugging agent according to claim 1, characterized in that: The temporary plugging agent matrix is selected from degradable polymers, preferably one of polyglycolide, polylactide, polybutylene succinate, polycaprolactone, polybutylene terephthalate-adipate, polybutylene terephthalate, polybutylene succinate adipate, polymethyl ethylene carbonate, polyhydroxyalkanoate, or a mixture thereof or a copolymer of their structural units.
3. The magnetic strengthening temporary plugging agent according to claim 1, characterized in that: The modified magnetic particles are magnetic particles modified by a compatibilizer. Preferably, the compatibilizer is selected from at least one of epoxy compounds, silane compatibilizers, copolymers containing maleic acid or its anhydride or its amide, titanate compatibilizers, aluminate compatibilizers, zirconate esters, borates, and aluminum-titanium composite compatibilizers; more preferably, based on 100 parts by weight of the magnetic particles, the compatibilizer is 0.1%-1% by weight, preferably 0.2%-0.6% by weight.
4. The magnetic strengthening temporary plugging agent according to claim 3, characterized in that: The magnetic particles are selected from at least one of ferrite, neodymium iron boron, samarium cobalt, aluminum nickel cobalt, manganese aluminum carbon, and iron chromium cobalt; and / or, The particle size of the magnetic particles is 100 to 800 nm, preferably 100 to 500 nm; and / or, In the magnetic strengthening temporary plugging agent, based on 100 parts by weight of the temporary plugging matrix, the modified magnetic particles are 5 to 30 parts by weight.
5. The magnetic strengthening temporary plugging agent according to any one of claims 1 to 4, characterized in that: The magnetically enhanced temporary plugging agent further comprises an elastic material coating coated on the surface of the temporary plugging agent matrix; preferably, the elastic material is selected from polymers containing ester bonds in the side chains, preferably polyvinyl acetate; more preferably, based on 100wt% of the temporary plugging agent matrix and the modified magnetic particles, the elastic material coating is 1-10wt%, preferably 3-5wt%.
6. The magnetic strengthening temporary plugging agent according to claim 5, characterized in that: The magnetically enhanced temporary plugging agent further optionally includes an auxiliary agent; preferably, the auxiliary agent is selected from at least one of an antioxidant, a stabilizer, and an anti-hydrolysis agent; more preferably, based on 100 parts by weight of the temporary plugging agent matrix, the antioxidant is 0.1%-1% by weight, the stabilizer is 0.001%-0.1% by weight, and the anti-hydrolysis agent is 0.1%-1% by weight.
7. A method for preparing the magnetically enhanced temporary plugging agent according to any one of claims 1 to 6, comprising: The temporary plugging agent matrix, the modified magnetic particles and the optional auxiliary agent are melt-blended, extruded and granulated, and then magnetized and optionally pulverized to obtain the magnetically enhanced temporary plugging agent.
8. The preparation method according to claim 7, characterized in that: The modified magnetic particles are obtained by mixing the compatibilizer with the magnetic particles, heating the temperature to 40-100° C., heat preservation, and drying to obtain the modified magnetic particles.
9. The preparation method according to claim 7, characterized in that: The magnetization treatment is carried out as follows: magnetization is performed in a magnetizer with a magnetization voltage of 0-2000V for more than 3 seconds.
10. The preparation method according to any one of claims 7 to 9, characterized in that: After the magnetization and optional crushing, the mixture is immersed in a solution containing the elastic material, filtered out, and dried to obtain the magnetically enhanced temporary plugging agent.
11. Use of the magnetically enhanced temporary plugging agent according to any one of claims 1 to 6 or the magnetically enhanced temporary plugging agent according to any one of claims 7 to 10 in fracturing.
Citation Information
Patent Citations
Magnetorheological fluid-based oil-gas well temporary plugging agent as well as preparation method and application thereof
CN103834375A
Enhanced temporary plugging agent capable of being used for wide cracks and preparation method thereof
CN111423863A
Self-cleaning degradable fracturing temporary plugging agent as well as preparation method and application thereof
CN111621272A
Clean temporary plugging agent as well as preparation method and application thereof
CN116463113A
Low-density, high-strength degradable temporary pugging agent and the preparation method and use thereof
US20190136116A1